Mental Health Problems Among School-Aged Children After School Reopening: A Cross-Sectional Study During the COVID-19 Post-pandemic in East China - Wang, Jingyi; Wang, Yingying; Lin, Haijiang; Chen, Xiaoxiao; Wang, Hao; Liang, Hongbiao; Guo, Xiaoqin; Fu, Chaowei (Frontiers in Psychology, 2021)
Background: Most studies on mental health problems caused by COVID-19 crisis in children were limited to the period of home quarantine. It remained unclear what adverse impact of the psychosocial stressors caused by school reopening, as well as the transitions in daily activities and social interactions had on mental health in children. Methods: A total of 6400 students in primary schools were enrolled in a cross-sectional study conducted in East China, between June 26 and July 6, 2020, when schools reopened. Children’s mental health status was assessed by the parent version of Strengths and Difficulties Questionnaire (SDQ). Ultimately, data on a total of 6017 children with completed information on mental health, psychosocial stressors, daily activities and social interactions were eligible for analysis. The associations of mental health with psychosocial stressors, daily activities and social interactions were determined by ordinal logistic regression models. Stratified analyses were conducted according to grade, gender, school level, area and caregiver-child relationship to further observe the effects of stressors on mental status. Results: The prevalence of borderline, moderately abnormal and prominently abnormal scores were 7.16%, 3.34% and 1.96% for total difficulties, and 13.83%, 13.45% and 17.85% for prosocial behavior, respectively. Children with psychological stressors had a significantly higher risk of being in a worse category of mental health status, with the maximum adjusted OR of 7.90 (95%CI 3.33-18.75) in those definitely afraid of inadaptation to study and life styles. Time used in home work and computer games was positively related to mental health problems, while physical exercises and frequency of communication with others was negatively related. The effects of psychological stressors on total difficulties were more evident in middle-high grade students (OR=7.52, 95%CI 4.16-8.61), boys (OR=6.95, 95%CI 4.83-8.55), those who lived in Taizhou (OR=7.62, 95%CI 4.72-8.61) and with poor caregiver-child relationship (OR=7.79, 95%CI 2.26-8.65). Conclusions: Emotional and behavioral difficulties, especially less prosocial behavior, were prevalent in primary school children after schools reopened. The Chinese government, communities, schools and families need to provide more effective support for students’ transition back into the school building and address emotional and behavioral problems for children with difficulties.